CHALLENGES AND STRATEGIES IN CHILDREN'S BIPA LEARNING ELEMENTARY SCHOOL LEVEL IN JAKARTA INDONESIA KOREAN SCHOOL - Muhammad Nur Alfi Syahri; Nuny Sulistiany Idris; Suci Sundusiah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to describe the challenges and strategies for learning Indonesian for Foreign Speakers (BIPA) in Jakarta Indonesia Korean School (JIKS), an international school based on the Korean curriculum whose participants are linguistically and culturally homogeneous. The main challenges in learning BIPA in JIKS include minimal interaction in Indonesian outside the classroom, the dominance of Korean language use in students' daily lives, and low learning motivation due to the position of BIPA subjects which are not included in the Korean core curriculum. This study uses a qualitative descriptive approach through literature studies, analysis of learning contexts, and reflection on teaching practices. The results show that the thematic-contextual approach is an effective and relevant strategy to overcome these challenges. This strategy includes the application of themes that are close to children's lives, simple project activities, contextual dialogues, role plays, Indonesian language habits in classroom routines, and the use of concrete media such as pictures and real objects. This approach allows students to understand the language in a real context, while building their confidence in using Indonesian. These findings are expected to be a reference for BIPA teachers in designing learning that is appropriate to the conditions of students in homogeneous international schools.